Crescimento somático e composição corporal de crianças estudantes da rede pública municipal de São José dos Pinhais, Paraná - Snége, Samara de Paula Neves Caetano (2021)
Percentile reference charts are widely used to assess and monitor the individual and collective growth of children and youth belonging to a given population. Due to the exponential increase in childhood overweight and obesity at a global level, there is a concern to portray more accurately the sociogeographic reality of populations, through detailed information from studies of physical growth and indicators of body composition. Therefore, the aim of this study was to construct percentile charts for body mass, height, body mass index (BMI), waist circumference (WC) and percentage of fat mass (%FM) and contrast with samples from the national and international context. Descriptive, quantitative, cross-sectional study carried out in 2019. A total of 2,294 children (1,173 girls) aged between five and 11 years old, students from the municipal public school system, were evaluated, 20 schools in the urban area and five schools in the rural area. Height, body mass, WC, triceps and calf adiposity folds were measured. Calculations for BMI and %FM were also performed. To identify possible differences between boys and girls, the t test was applied for independent samples and analysis of variance to verify the average differences between the ages, followed by the post hoc Bonferroni test. The level of significance established was 5%. For the construction of the percentile charts, the LMS method, implemented in the LMSchartmaker software, was used to compare the percentile values referring to the variables of somatic growth and body composition with national and international samples. In general, boys and girls increase the mean values of measures of height, body mass, BMI, BW and %FM with age design. Boys had higher mean values of CP (t = - 5.0001); ) and %MG (t = 9.110; p < 0.001). In relation to the folds, girls show an increase with age (f = 20.364; p<0.001), higher than boys. In relation to the CDC and WHO samples, as children from São José, similar height values were found; as for weight and BMI, the values are higher from 8 years of age for girls and 6 years of age for boys. International comparisons and the level of national importance are the strong variability in the percentages in each discrete value of, both in reference to girls and in the study of each group of children and young people closest to them. . In this way, the use of the normative values presented in this study, in an associated way with the internationally for the clinical context, can help an educational and sports pedagogical action of the Physical Education teacher, in the monitoring of the growth indicators and body composition of the students, in a way individual and collective.